KEJADIAN MUSCULOSKELETAL DISORDERS (MSDS) DITINJAU DARI POSISI KERJA PADA PENJAHIT DI PT GARMENT BATAM TAHUN 2024 - Rusdani; nopri, Nopri Esmiralda; Aziz Saputra (Universitas Batam, 2025)
ABSTRACT Background: Musculoskeletal Disorders (MSDs) are common health issues that can cause discomfort in joints, muscles, bones, cartilage, ligaments, and nerves. Workers in the textile industry, especially in the convection bussiness, are at high risk of developing MSDs due to less ergonomic working positions. Methods: This research uses quantitative methods with a cross-sectional design to assess the relationship between work position and MSD complaints among tailors at PT Garment Batam in 2024. The sampling method used is total sampling, where all 43 tailors at PT Garment Batam are included as research subjects. The chi-square and fisher test will be used for statistical analysis. Results: Based on the results of the fisher test, a p-value of 0.005 (p < 0.05) was obtained. This indicates a significant relationship between work position and musculoskeletal disorder complaints among tailors at PT Garment Batam in 2024. Conclusion:. This research concludes that poor working positions can increase the risk of Musculoskeletal Disorder (MSD) complaints among tailors at PT Garment Batam in 2024. Keywords: Work Posture, complaints of musculoskeletal disorders, Tailors